Tourism with Energy Production and Consumption in the Red River Delta, Vietnam - Thuy, Duyen Dang Thi; Thu, Huyen Giang Thi (International Journal of Energy Economics and Policy, 2023)
Tourism development is always the leading development orientation in Vietnam and many countries. Has tourism developed sustainably and how can tourism develop sustainably? In the development process, tourism consumes more energy due to various tourism activities such as hotel accommodation and transportation. How does energy production affect tourism growth? This question is asked of any country and economic region. This study investigates the long-term cointegration relationship between tourism growth and primary energy consumption. This study aims to examine the factors affecting tourism growth in the Red River Delta, Vietnam such as the energy production, gasoline consumption, tourism labor, tourism investment capital and gross domestic product. The study uses a model with secondary data of 11 provinces from 2010-2020. The experimental results demonstrate that the independent variables explain 51% of the variation of the dependent variable and the rest (49%) can be explained by other causes. Research results show that 2 factors, labor (L), investment capital (IN), have a positive impact on tourism growth. Energy production (EN) has a negative impact on tourism growth in the Red River Delta. From there, the author will propose possible solutions that can ensure labor, investment capital and rational use of energy for tourism development.